An advanced quadratic displacement approach for the analytical stress analysis of adhesive bonded joints. Issue 1 (14th December 2021) - Methfessel, Thomas S.; Becker, Wilfried
Abstract: In this work an advanced analytical model for the efficient prediction of stress distributions in the adhesive layer of bonded joints is presented. In order to better account for local deformation effects occurring in thicker adhesive layers, a quadratic‐extended displacement approach is introduced. The use of a general sandwich‐type model for the overlap region enables a wide applicability to the analysis of different joint shapes and load cases.